Effectiveness of Group Hope Therapy on Quality of life and Resilience in Addicted Women - Zeynab Dehghani; Anahita Khodabakhshi-koolaee (Hamadan University of Medical Sciences, 2017)
Background and Objectives: Hope therapy as a positive psychological intervention can be helpful in reducing the psychological problems in addicted people. Therefore, the present study was conducted with the aim of investigating the effectiveness of group hope therapy on quality of life and resilience in addicted women. Materials and Methods: This semi-experimental study was conducted on 30 addicted women who referred to the Rehabilitation Center of Varavard, Tehran, Iran, using the pretest-posttest design and a control group. The participants were divided into experimental and control groups based on the obtained scores regarding the quality of life and resilience. The data were collected using the World Health Organization Quality of Life and Connor -Davidson Resilience Scale. Data analysis was performed by analysis of covariance in SPSS, version 20. Results: According to the results, the mean quality of life (F=54.42, P<0.01) and resilience (F=7.02, P<0.01) significantly increased in the intervention group at the posttest stage. Nonetheless, no significant difference was observed in the control group in this regard. Conclusion: As the findings indicated, group hope therapy could improve the quality of life and resilience in the addicted women. In addition, this therapy could enforce the addicted people to achieve the positive self-concept and actualize their positive potential ability. Consequently, the mental health professionals are recommended to use this intervention along with other pharmaceutical and non-pharmaceutical therapies to improve the quality of life and resilience in the addicted women.